Research handbook on transnational corporations - De Jonge, Alice; Tomasic, Roman; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
Transnational corporations (TNCs) have moved to the forefront of regulatory governance both within states and in the international arena. The Research Handbook on Transnational Corporations provides expert background commentary and up-to-date insights into regulatory frameworks impacting on TNCs at global, industry and national levels. Written by global experts in their field, this unique collection of essays provides in-depth understanding of how the forces of globalisation affect the world's largest corporations, and how those corporations, in turn, shape globalisation. Comprehensive yet highly accessible, this is the first major work on the reciprocal impact of TNCs on regulatory processes. The Research Handbook provides guidance on how best to understand the rapidly evolving relationship between TNCs and the processes of treaty making, the formation of global industry standards and the processes of national law making and policy formation (with a focus on resource taxation). Global, industry and national-level case studies are used to explain the basic principles used to support state, private, and international regulatory programs. Delivering both theoretical and practical insights into the regulation of TNCs, this timely and authoritative Research Handbook will be of particular interest to policy makers, industry practitioners and lawyers. Students and academics will also find it to be an invaluable resource.
Introduction: understanding transnational corporations in the 21st century / Alice de Jonge and Roman Tomasic -- 1. The evolving nature of the transnational corporation in the 21st century / Alice de Jonge -- 2. Theoretical approaches to global regulation of transnational corporations / Rachel J. Anderson -- 3. The evolving relationship between TNCs and political actors and governments / Larry Catá Backer -- 4. The global compact / Maria Alejandra Gonzalez-Perez and Liam Leonard -- 5. The equator principles and the 'business and human rights debate': hype or hope? / Manuel Wörsdörfer -- 6. Group companies: supply chain management, theory and regulation / Jodie A. Kirshner -- 7. Global sourcing through foreign subsidiaries and suppliers: challenges for corporate social responsibility / Andreas Rühmkorf -- 8. How the transnational pharmaceutical industry pursues its interests through international trade and investment agreements: a case study of the Trans-Pacific Partnership / Deborah Gleeson, Pat Neuwelt, Erik Monasterio and Ruth Lopert -- 9. A case in supply chain and business sustainability: Samsung's management of human rights in consumer electronics manufacturing / Anna Chou -- 10. China's investment traditions and the modern transnational corporation / Megan Bowman, George Gilligan, and Justin O'Brien -- 11. Capital market disclosure regimes: advancing accountability for Chinese TNCs / Virginia Harper Ho -- 12. Transnational corporations and mining tax reform: the story of the Australian mineral resources rent tax revolt / Roman Tomasic -- 13. Risks and fiscal concerns in the extraction of natural resources: a study of transnational corporations in Papua New Guinea / Diane Kraal -- Index.
Contributors include: R. Anderson, M. Bowman, L. Catá Backer, A. Chou, A. De Jonge,G. Gilligan, D. Gleeson, M.A. Gonzalez-Perez, V. Harper Ho, J.A. Kirshner, D. Kraal, L. Leonard, R. Lopert, M.E. Monasterio, P. Neuwelt, J. O'Brien, A. Rühmkorf, R. Tomasic, M. Wörsdörfer
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: nadnárodní společnosti; international business enterprises; e-knihy online; e-books online